Cooperation Dilemma: Between Islamic Values and Digitalization - Adlan, Muhamad Aqim (Tribakti: Jurnal Pemikiran Keislaman, 2023)
This study aims to look again at the existence of cooperation in the digital era in an Islamic economic review. Because in the current contemporary era, cooperation activities have experienced a decline caused by the onslaught of new competitors who utilize digital technology. This condition is, of course, a concern in itself because cooperation is an economic institution initiated by the nation's founding fathers and stipulated in the 1945 Constitution of the Republic of Indonesia (UUD 1945) which is in principle in line with Islamic economic values. Therefore, in the current contemporary era, cooperation is expected to be able to adapt in the digital context and the industrial revolution 4.0. Qualitative research with this type of case study reveals the implementation of cooperation systems in the digital era in three different cooperation, both in terms of operating principles and their basis. The findings in this study indicate that the implementation of cooperation in the three objects still needs to be optimally able to adapt to digital technology. The Islamic economic value has been carried out for cooperation that runs it while for others using state rules and regulations.